An Atypical Presentation of Primary Hyperparathyroidism in an Adolescent: A Case Report of Hypercalcaemia and Neuropsychiatric Symptoms Due to a Mediastinal Parathyroid Adenoma - Minelli, Roberta; Meoli, Aniello; Tiri, Alessandra; Fanelli, Umberto; Iannarella, Rosanna; Gismondi, Pierpacifico; Esposito, Susanna (Frontiers in Endocrinology, 2020)
Psychiatric disorders are rare clinical manifestations of hypercalcaemia in the paediatric population, are relatively more frequent during adolescence and are often overlooked in cases of severe hypercalcaemia. We described the case of a 17-year-old girl affected by anorexia nervosa, depression and self-harm with incidental detection of moderate hypercalcaemia. Clinical, laboratory and instrumental tests demonstrated that hypercalcaemia was secondary to primary hyperparathyroidism (PHPT) due to a mediastinal parathyroid adenoma in the thymic parenchyma. After parathyroidectomy with robot-assisted surgery, we observed the restoration of calcium and PTH levels in addition to an improvement in psychiatric symptoms. This case demonstrates that serum calcium concentration should be evaluated in adolescents with neurobehavioural symptoms and in cases of hypercalcaemia PHPT should be excluded. Surgery represents the cornerstone of the management of PHPT and may contribute to improving quality of life and psychological function in these patients. However, the complexity of neurological involvement in cases of hypercalcaemia due to PHPT requires further investigations to establish the real impact of this condition on the neurocognitive sphere.